Keterampilan Mendesain Proyek Rounding Board Materi Matematika Di Sdn Kahakan Kalibaru - Ghaida Fatimah; Darmiyati Darmiyati (CV. ITTC INDONESIA, 2024)
The problem in this research is the lack of critical thinking skills and fear of making mistakes in completing assignments. The aim of this research is to describe teacher activities, student activities, critical thinking skills and improving student learning outcomes at IV SDN Kahakan Kalibaru. Researchers used a qualitative approach with the PTK type carried out at SDN Kahakan Kalibaru with research subjects of 27 grade IV students in the 2023/2024 academic year. This type of research includes qualitative data obtained from observing teacher and student activities and critical thinking skills, quantitative data obtained from student learning outcomes through written tests. The data was analyzed using a percentage scale and success indicators determined by the researcher. The research results showed that at the last meeting the teacher's activities had been successful and reached the